Attitudes toward uncertainty among the poor: evidence from rural Ethiopia - Akay, Alpaslan; Martinsson, Peter; Medhin, Haileselassie; Trautmann, Stefan T. (Discussion paper series, 2009)
We looked at risk and ambiguity attitudes among Ethiopian peasants in one of the poorest regions of the world and compared their attitudes to a standard Western university student sample elicited by the same decision task. Strong risk aversion and ambiguity aversion were found with the Ethiopian peasants. Ambiguity aversion was similar for peasants and students, but peasants were more risk averse. Testing for the effect of socio-economic variables on uncertainty attitudes showed that poor health increased both risk and ambiguity aversion. -- Risk attitudes ; ambiguity attitudes ; poverty ; cultural differences
Keywords: Arbeitspapier; Graue Literatur